2018
DOI: 10.1007/s00384-018-3014-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with longer cecal intubation time: a systematic review and meta-analysis

Abstract: The current meta-analyses have demonstrated that old age, female sex, low BMI, and poor bowel preparation were the predictors for prolonged CIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
1
26
2
Order By: Relevance
“…A previous meta-analysis found that a lower BMI is associated with a longer CIT. [ 18 ] In contrast, our study did not find any significant association between anthropometric data and prolonged CIT. Therefore, the amount of abdominal fat or muscle did not affect the difficulty of colonoscopy in expert colonoscopists.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A previous meta-analysis found that a lower BMI is associated with a longer CIT. [ 18 ] In contrast, our study did not find any significant association between anthropometric data and prolonged CIT. Therefore, the amount of abdominal fat or muscle did not affect the difficulty of colonoscopy in expert colonoscopists.…”
Section: Discussioncontrasting
confidence: 99%
“…One recent meta-analysis study reported older age, female sex, low BMI, and poor bowel preparation as factors significantly associated with a longer CIT. [ 18 ] We hypothesized that optimal bowel preparation leads to decreased procedure time (from insertion to withdrawal) and increased polyp detection rate. We found a positive correlation between old age and poor bowel preparation and prolonged CIT.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,7,8 Leading causes of incomplete colonoscopy include; inadequate colon cleansing, advanced age, female gender, low body mass index (BMI), previous abdominal or pelvic surgery, diverticulosis, long-tortious colon, procedure without sedation and inexperienced endoscopist. 9,10,11,12,13,14 In our endoscopy unit, approximately 2000 colonoscopes are performed annually. It is important that clinics assess their own results, observe compliance with quality standards in the colonoscopy, and correct any deficiencies that are identified.…”
Section: Introductionmentioning
confidence: 99%
“…Colonoscope insertion time is an important technical measure of colonoscopy. 28 Although the technical difficulty of colonoscope insertion was not recorded by the colonoscopists, the longer insertion time in the gastric cancer group indirectly suggests that colonoscope insertion was more technically demanding in postgastrectomy patients than in the healthy population. We investigated colonoscope withdrawal time only in patients who did not undergo any additional procedures such as a biopsy or polypectomy.…”
Section: Discussionmentioning
confidence: 98%